Analisis Perluasan Makna Pasal 71 Ayat (1) Undang-Undang Pilkada Berdasarkan Putusan Pengadilan Negeri: Upaya Mewujudkan Keadilan Dalam Pilkada 2024 - Supriyadi, Supriyadi; Iskandar, Abdullah (Jurnal Hukum & Pembangunan, 2025)
The analysis and study of decisions is actually popular and developed in countries with common law systems, legal scholars, researchers and practitioners there place their court decisions as the primary object of legal study, which is why the existence of court decisions is the main benchmark in applying and shaping the law. In the context of legal development in Indonesia, the study of this decision has had a good place among legal scholars and researchers, this has been proven by the existence of several works produced focusing on the analysis of decisions, such as those popularised by the Judicial Commission of the Republic of Indonesia by involving several campuses in Indonesia to conduct analysis of district court decisions under the Supreme Court. As usual, this research aims to examine and find the characteristics of judges' interpretations of the elements of Article 71 paragraph (1) of the Pilkada Law from various court decisions. This research is a normative research but by prioritising decisions as primary legal material. The results of this study are: first, there has been a shift in theoretical and legislative science regarding the concept of crossing norms between Article 71 paragraph (1) and Article 188, which was theoretically interpreted as primary and secondary norms, now after the decision of the District Court, both norms are primary norms. Second, there is an expansion of the meaning of the provisions of Article 71 paragraph (1) of the Local Election Law in terms of the meaning of the subject element and the meaning of the object of the norm and the condition of the norm.